Medicinal plants : phytochemistry, pharmacology and therapeutics - Gupta, V. K. (Vijay Kumar), 1953-; Singh, G. D. (Gur Darshan), 1962-; Surjeet Singh, 1958-; Kaul, A. (Anpurna), 1956- (Delhi : Daya Pub. House, 2010)
Contributed articles.
Includes bibliographical references and index.
Keywords: Materia medica, Vegetable